Pengaruh Return On Asset, Dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Sektor Industri Barang Komsumsi Yang Terdaftar Di Bursa Efek Indonesia - Agnes Mayjesti; Elisabet Pali; Adriana M Marampa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The problem in this study is whether ROA and EPS affect stock prices in Industrial Sector Companies Listed on the Indonesia Stock Exchange, the type of research used in this study is Quantitative research and using a sample of 40 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange that have been tested through purvosive sampling criteria. Multiple linear regression analysis and SPSS version 26 are the analyses used in this study so that they show the results of hypothesis testing, namely that ROA partially has an effect and is significant on stock prices, and EPS has a positive and significant effect on stock prices. Simultaneously, ROA and EPS have a positive and significant effect on share prices in companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange in 2022.